Quantitative Raman Spectroscopy Analysis of Polyhydroxyalkanoates Produced by Cupriavidus necator H16 - Ota Samek; Stanislav Obruča; Martin Šiler; Petr Sedláček; Pavla Benešová; Dan Kučera; Ivana Márova; Jan Ježek; Silva Bernatová; Pavel Zemánek (Sensors, 2016)
We report herein on the application of Raman spectroscopy to the rapid quantitative analysis of polyhydroxyalkanoates (PHAs), biodegradable polyesters accumulated by various bacteria. This theme was exemplified for quantitative detection of the most common member of PHAs, poly(3-hydroxybutyrate) (PHB) in Cupriavidus necator H16. We have identified the relevant spectral region (800–1800 cm−1) incorporating the Raman emission lines exploited for the calibration of PHB (PHB line at 1736 cm−1) and for the selection of the two internal standards (DNA at 786 cm−1 and Amide I at 1662 cm−1). In order to obtain quantitative data for calibration of intracellular content of PHB in bacterial cells reference samples containing PHB amounts—determined by gas chromatography—from 12% to 90% (w/w) were used. Consequently, analytical results based on this calibration can be used for fast and reliable determination of intracellular PHB content during biotechnological production of PHB since the whole procedure—from bacteria sampling, centrifugation, and sample preparation to Raman analysis—can take about 12 min. In contrast, gas chromatography analysis takes approximately 8 h.